Is it Luring Innovations or just Profit? The Case of European Patent Boxes - Michael Stimmelmayr; Marko Koethenbuerger; Federica Liberini (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The effectiveness of European patent boxes in triggering R&D and fostering new patentable innovations is the subject of a growing debate. These regimes are considered liable of tax-favouring already successful ideas, without imposing a nexus between the final location of the intellectual property (IP) and its related innovation. This paper brings the debate forward onto the assessment of the quantitative impact of patent box regimes on profit shifting by multinational firms. Our empirical strategy builds on a difference-in-difference model comparing the pre-tax profit of European subsidiaries affiliated to firm conglomerates that owned patents long before the introduction of IP boxes, to that of European subsidiaries affiliated to firm conglomerates with no historical record of patent ownership. We find that European subsidiaries affiliated to foreign IP owners report, after the introduction of a local patent box, on average 2.5 to 3.9 percent higher profit compared to European subsidiaries affiliated to non-IP-owning conglomerates. For countries where the patent box regime incorporates a nexus clause, i.e. grants the IP related tax benefit only to newly created IP, we find no significant difference in the profits of the two groups.
Keywords: H26; F23; C23; 330